Pengaruh Kepemilikan Keluarga dan Kepemilikan Asing terhadap Pengungkapan Corporate Social Responsibilitypada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia - Adelia Pramita Sari (JURNAL EKOMBIS, 2018)
Abstract:The purpose of the study is to examine the effect of family ownerships and foreign ownerships on corporate social responsibility disclosure in Manufacturing Companies at Basic Industry and Chemical Sector listed in Indonesia Stock Exchange. The study hypothesized that there is positive effect of family and foreign ownerships on CSR disclosures level. The sample of the study consist of 40 annual report at 2012 manufacturing companies listed in Indonesia Stock Exchange. The empirical results of the study show that family ownership is significantlyeffect thedisclosureof corporate social responsibility(CSR). However, the coefficientsare negative. Foreign ownership is notsignificantlyeffect thedisclosure ofcorporate social responsibility (CSR).  Keywords: Corporate Social Responsibility, Family Ownerships, Foreign Ownerships